Host-pathogen interaction: How EHEC influence the actin cytoskeleton of the host cell Wirt-Pathogen-Interaktion wie EHEC das Aktinzytoskelett der Wirtszelle beeinflussen - Stradal, Theresia E.B.; Backert, Steffen (BioSpektrum, 2010)
Two types of pathogenic Escherichia coli (EPEC and EHEC) firmly attach to gut epithelial cells and induce pedestals, which are actin-rich structures protruding beneath attached bacteria. The different strategies of EPEC and EHEC to induce pedestals are discussed.
CRIS-Team Scopus Importer:2020-09-18